Chimeric Antigen Receptor T Cell Based Immunotherapy for Cancer - Li, Feng; Zhang, Tengfei; Cao, Ling; Zhang, Yi (Current Stem Cell Research & Therapy, 2018)
Cancer immunotherapy, a new weapon against cancers by harnessing the patient's own immune system, potentiates an extended remission and possibly a cure for cancer. T cells genetically engineered with chimeric antigen receptor (CAR) vectors can specifically target the surface antigen of cancer cells and kill them in an MHC-independent manner. CD19 is extensively expressed on cancerous cells in B cell malignancies. To target this antigen, CAR T cells have gained great success in treating patients with B cell leukemia and lymphoma. Currently, the data from clinical trials on CAR T cells in solid tumors are limited; thus, CAR T cells targeting GD2, HER2, EGFRvIII, CSPG4, DNAX, mesothelin, and other molecules are under active investigation for solid tumors. In this review, we summarize the clinical results for CAR T cells in the case of hematologic and solid tumors, along with the current developments in CAR T cell immunotherapy.
Keywords: cancer cells